The extent of carbapenem-resistant encoding genes in Klebsiella pneumoniae from COVID-19 and non-COVID-19 patients in a tertiary care center, Saudi Arabia - A. Al Bshabshe; M.E. Hamid; E. Salem; I.M. Abdelrahim; M. Assiry; A. Alasmari; M. Joseph; Y. Alhammdi (Brazilian Journal of Medical and Biological Research)
Rapid dissemination of Klebsiella pneumoniae carbapenemase (KPC) is a leading cause of treatment failure, significantly increasing morbidity and mortality rates among inpatients, particularly in the intensive care unit (ICU). This study aimed to detect the occurrence of carbapenemase- and carbapenem-resistant-encoding genes in K. pneumoniae isolates from COVID-19 positive and negative patients, and to assess their impact on patient outcomes. A prospective analysis was conducted at a tertiary care hospital in Saudi Arabia, collecting 97 carbapenem-resistant K. pneumoniae (CRKP) isolates from patients with COVID-19 during 2020-2021. Isolates were obtained from various clinical specimens. Antimicrobial susceptibility assays were performed using the Automated Vitek-2 system, and data were analyzed using IBM SPSS Statistics. The predominant carbapenemases identified were Oxacillinase-48 (OXA-48), followed by KPC and New Delhi metallo-β-lactamase (NDM), with Imipenemase (IMP) and Verona integron-encoded metallo-β-lactamase (VIM) being the least prevalent. COVID-19 did not significantly affect the distribution of these genes (P>0.05); however, COVID-19 status and age over 60 years significantly impacted the outcomes of CRKP patients. Other factors such as gender, total ICU or ward stay, and comorbidities did not significantly affect CRKP infection outcomes. The most common carbapenem-resistant genes identified were blaKPC, blaNDM, and blaOXA-48; however, they were not significantly associated with increased mortality.